Smart aid safety vest - Che Ahmad, Nor Alif Hakimie; Othman, Mohamad Hamdan (2024)
This detailed study explores the Smart Aid Safety Vest, focusing on its development, evolution, and adoption in the construction industry. The methodology employed involves rigorous experimentation, wherein the vest's efficiency and precision in ensuring worker safety undergo meticulous evaluation within a controlled setting. Our design framework incorporates features aimed at enhancing problem-solving capabilities and providing factual visualizations aligned with predefined research parameters. Extensive desk research provides invaluable insights into public perception, practical applications, pricing structures, capabilities, and commercial availability. The meticulous analysis of data serves as a cornerstone in advancing the Smart Aid Safety Vest, shedding light on technological intricacies, safety process efficacy, and the vest's adaptability to diverse environments. The design study meticulously examines the conceptual underpinnings of the project, encompassing structural components, navigation techniques, safety methodologies, and the utilization of simulations to gauge performance across various scenarios. Ergonomics and user interface considerations are carefully integrated into the design, resulting in a solution that aligns seamlessly with project objectives. This avant-garde solution, crafted through collaborative efforts among domain specialists, is meticulously detailed within the report's chapters. The research findings not only enrich the burgeoning realm of safety technologies in construction but also underscore the paramount importance of innovative design and evidence-based decision-making in fostering excellence in construction safety.